The Influence of Work Motivation and Competence on the Performance of School Administration Personnel (A Study on Public SMASMK in South Minahasa Regency) - Karaeng, Julianto; Bogar, Wilson; Wawointana, Thelma (Technium Social Sciences Journal, 2025)
This study aims to determine the effect of work motivation (X1) and Competence (X2) on the performance of school administration personnel (Y), both partially and simultaneously. This research is a type of quantitative research using the survey method. This study uses population sampling technique, namely respondents are the total population, which in this study amounted to 126 administrative staff of public Senior High School (SMA)/Vocational High School (SMK) in South Minahasa Regency. The results showed that 1) Work motivation (X1) has a positive and significant effect on the performance of school administration personnel (Y) in public SMA/SMK in South Minahasa Regency. This means that the higher the work motivation of the administrative staff, the higher the performance shown. Conversely, if work motivation decreases, the performance of administrative staff will also decrease. 2) Competence (X2) has a positive and significant effect on the performance of school administration personnel (Y) in public SMA/SMK in South Minahasa Regency. This means that the higher the competence of the administrative staff, the higher the performance shown. Conversely, if competence decreases, the performance of administrative staff will also decrease. 3) Simultaneously work motivation (X1) and competence (X2) have a positive and significant effect on the performance of school administration personnel (Y) in public SMA/SMK in South Minahasa Regency. This means that if work motivation and competence increase simultaneously, the performance of school administration personnel will also increase. Conversely, if work motivation and competence decrease simultaneously, the performance of administrative staff will also decrease. The results of calculating the coefficient of determination (R2) obtained by the results R2=0,554 means that performance 55,40% is determined by work motivation and competence, and 44,60% by other factors not examined in this study.